Recent Unemployment Experience in New Zealand - Jeff Borland (New Zealand Government, The Treasury, 2014)
This paper discusses the recent history of the rate of unemployment in New Zealand. The rate of unemployment in New Zealand increased by about 3.5 percentage points between late 2007 and late 2009, and then has remained relatively steady to early 2013. Compared to the most recent previous downturn in the late 1990s, this episode in the late 2000s has involved a larger increase in the rate of unemployment and much smaller subsequent reduction. This paper argues that changes to the rate of New Zealand unemployment can be explained entirely by economic growth outcomes, and do not seem to reflect any structural change in the labour market. This suggests that there are not any impediments to the rate of unemployment falling back to levels that existed in the mid- 2000s. Of course, should the rate of unemployment remain at its current level for a prolonged period, hysteresis effects associated, for example with a growing incidence of long-term unemployment, may have some influence.
Keywords: J63; J64; 330; Unemployment; matching; Okun's relationship